Science in educational activities: the way to quality education - Шуст, Наталія Борисівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article deals with the role of science in educational activities, namely the ability to create and make university education institution in the cleansed as it is understood throughout the world.